Digital Literacy and Educational Technology: Fostering Historical Awareness and Charavter Building in Social Sciences Education Students at Islamic Higher Education Institutions - Fatmi Fauzani Duski; Aulia Rahmi Putri; Nurbaiti Nurbaiti; Nadyatul Fitria Siregar; Irfan Fathurrahman (UIN Imam Bonjol Padang, 2025)
The digital era brings new challenges and opportunities in education, especially in character development and digital literacy of students. This study aims to determine the level of digital literacy of students of Social Studies Education Study Program in Islamic Universities and analyze its influence on students' character development in the digital era. The results of the study show that the level of digital literacy of students is still classified as low to moderate. Although some students have used technology for academic needs, only a small number are able to optimally integrate technology in the learning process and character development. Factors that influence low digital literacy include limited access to digital devices and the Internet, as well as limited understanding of how to use technology effectively. This study highlights the importance of integrating digital literacy into the curriculum, teacher training, and institutional support to create digitally literate students with strong character. The implications of these findings provide a basis for developing strategies to strengthen digital literacy based on character education in Islamic higher education